Pengaruh Motivasi Kerja terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Intervening pada Puskesmas Pulorejo - Helmi Buyung Aulia Safrizal; Rima Rohmatul Laili (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
TheÂ  study discusses the problems that exist in Pulorejo Public Health Center of Ngoro, Jombang. The problems that exist in this Public Health Center are low work motivation and job satisfaction. There are 3 variables in this study, namely work motivation as an independent variables, job satisfaction as an intervening variable and employee performance as the dependent variable.Â  The objective of this study is to determine the effect of work motivation on employee performance with job satisfaction as an intervening variable. This study uses a quantitative approach with path analysis and a sample of 73 respondents. Based on the results of data processing and analysis, it can be concluded that (1) Work motivation has a positive and significant effect on the employee performance of Pulorejo Public Health Center, (2) Work Motivation has a positive significant effect on job satisfaction of Pulorejo Public Health Center, (3) job satisfaction has a positive and insignificant effect on the employee performance of Pulorejo Public Health Center, (4) The indirect effect of work motivation is positive and insignificant on the employee performance of Pulorejo Public Health Center.